Urban bee functional groups response to landscape context in the Southeastern US - Braman, Charles A.; McCarty, Elizabeth; Ulyshen, Michael D.; Janvier, Amy Joy; Traylor, Clayton; Edelkind-Vealey, Miriam; Braman, S. Kristine (Frontiers in Sustainable Cities, 2023)
Abstract • We investigated the influence of landscape cover on urban bee community functional groups • We observed a diversity of functional groups across primarily forested and primarily urban sites, however particular species were favored by forest/urban spaces • Results point to the importance of further investigating the nuance of land use impacts on pollinator communities, and in particular demonstrates the merit of investigating landscape heterogeneity • Conservation of forest remnants in urban environments can positively impact wild bees across multiple functional groups